Mental Health Literacy Programs for Parents of Adolescents: A Systematic Review - Kusaka, Sakurako; Yamaguchi, Satoshi; Foo, Jerome Clifford; Togo, Fumiharu; Sasaki, Tsukasa (Frontiers in Psychiatry, 2022)
Introduction: Many mental illnesses begin during adolescence. Parents of adolescents need to have sufficient mental health literacy (MHL) to recognize mental health problems in their children and to assist them with help-seeking. Although several educational programs have been developed to enhance parental MHL, their effectiveness has not been established. This study provides a systematic review for the effectiveness of MHL programs in parents of adolescents. Methods: PubMed, PsycINFO, CINAHL, ERIC and Web of Science were searched from the earliest date possible until February 2022; references of studies which met eligibility criteria were also screened. Studies that assessed quantitative change in at least one of the following components of parental MHL were included: knowledge of mental health/illnesses; stigma towards people with mental health problems; confidence in helping children with mental health problems, and intention, knowledge or behavior of helping children with mental health problems. Risk of bias (ROB) for each outcome within the included studies was rated using the revised Cochrane risk-of-bias tool for randomized controlled trials (RCTs), and the Risk of Bias Assessment Tool for Nonrandomized Studies for nonrandomized studies. Results: Nine studies (4 RCTs, 3 controlled before-and-after studies, and 2 case series), reported in 10 articles, were included. Mental health knowledge and/or confidence was significantly improved in several studies, while no studies observed significant improvement in stigma and/or intention/behavior of helping children. ROB was high in 5 out of 9 studies (10 out of 18 outcomes) and unclear in the others, mainly due to the lack of information on methods and results. Conclusions: A limited number of studies have evaluated effects of MHL program in parents and inconsistent quality contributes to difficulty in establishing their overall effectiveness. More studies with appropriate methods of recruitment, measurement and analysis, and transparent reporting are needed.